The Development of Teaching Materials Poetry Reading Based on Contextual Approaches in 8th Grade Students of Junior High School 1 Pancur Batu - Susi Yanti Br Sinuraya; Khairil Anshari; Wisman Hadi (BIRCU, 2020)
In the form of an assessment guide reading poetry on poetry text material and knowing the process of developing and the feasibility of the product. This research method is a Research and Development (R&D) research and development method proposed by Tegeh et al. Referring to the Borg & Gall model with minor adjustments according to the research context simplified to product trials. Data was collected through validation of material experts, design experts, the responses of Indonesian Language teachers of Junior High School 1 Pancur batu, and 32 students of Junior High School 1 Pancur batu as research subjects. The results of this research and development are teaching materials in the form of textbooks based on contextual approaches in the form of printed media, which have been declared feasible to be used by material experts, design experts, Indonesian language teachers and students as learning resources. The feasibility of teaching materials in accordance with the results of validation. The results of the expert validation of the material include a component of content worthiness with an average of 82.29% in the very good criteria, the feasibility of the presentation obtained an average value of 82.5% in the very good criteria, the feasibility of the language obtained an average value of 86.11% in the very good criteria , and contextual feasibility obtained an average value of 81.25 on very good criteria.